Review of Land Administration Data Dissemination Practices: Case Study on Four Different Land Administration System Types - Josip Križanović (MDPI AG, 2021)
Land administration systems differ by their types and practices. The data dissemination practices are considered to be outdated, as in most cases the digitisation of land administration data was conducted to match the paper-based system. This paper reviews four different land administration data dissemination practices through four case studies, where each selected jurisdiction represents one land administration system type. The analysed LAS data dissemination practices were conducted for Croatia, England, New Zealand and Green County, OH, USA. The main goal of the analysis was to examine the differences and similarities between the respective countries’ land data practices provided by the excerpts related to one parcel. The identified differences and similarities might be of great use when it comes to further improvement and standardisation of land administration data dissemination practices.